2019
DOI: 10.1016/j.devcel.2019.09.018
|View full text |Cite
|
Sign up to set email alerts
|

N-WASP Control of LPAR1 Trafficking Establishes Response to Self-Generated LPA Gradients to Promote Pancreatic Cancer Cell Metastasis

Abstract: SummaryPancreatic ductal adenocarcinoma is one of the most invasive and metastatic cancers and has a dismal 5-year survival rate. We show that N-WASP drives pancreatic cancer metastasis, with roles in both chemotaxis and matrix remodeling. lysophosphatidic acid, a signaling lipid abundant in blood and ascites fluid, is both a mitogen and chemoattractant for cancer cells. Pancreatic cancer cells break lysophosphatidic acid down as they respond to it, setting up a self-generated gradient driving tumor egress. N-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
61
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(65 citation statements)
references
References 67 publications
4
61
0
Order By: Relevance
“…We recently showed that Wasl deletion impairs ADM by inhibiting fluid-phase endocytosis in pancreatic acinar cells (6). Juin and colleagues created a conditional mouse model with a mosaic deletion of Wasl and concomitant activation of oncogenic Kras and mutated p53 (Trp53 R172H ) (KPCN mice) (9). In this KPCN model, Wasl loss deregulated vesicular transport, reduced metastasis, and improved survival.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We recently showed that Wasl deletion impairs ADM by inhibiting fluid-phase endocytosis in pancreatic acinar cells (6). Juin and colleagues created a conditional mouse model with a mosaic deletion of Wasl and concomitant activation of oncogenic Kras and mutated p53 (Trp53 R172H ) (KPCN mice) (9). In this KPCN model, Wasl loss deregulated vesicular transport, reduced metastasis, and improved survival.…”
Section: Discussionmentioning
confidence: 99%
“…Mice. Ptf1a Cre/wt , Kras LSL-G12D/wt , Trp53 fl/fl , and Wasl fl/fl strains have previously been described (6,9,20,34,68,69).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The significance of the ubiquitously-expressed N-WASP in protrusion is less clear. N-WASP appears to be critical for 3D invasion [94][95][96], and N-WASP may contribute to 2D motility by some cells [89], but knockouts in mouse fibroblasts and knockdowns in several cancer cell lines suggest that N-WASP is dispensable for lamellipodial assembly [20,97,98]. On the other hand, phylogenetic and functional analyses indicate that the presence of both the WAVE and WASP subfamilies is necessary for fast pseudopod-based amoeboid-like motility [27].…”
Section: Discussionmentioning
confidence: 99%
“…LPA, a bioactive phospholipid binds to a variety of GPCRs to trigger multiple cellular processes such as survival, differentiation, embryonic development and migration (Aikawa et al, 2015). A major constituent of serum, LPA has been implicated in initiation and progression of malignant diseases and is a potent chemoattractant to different cell types including tumor cells (Muinonen-Martin et al, 2014;Juin et al, 2019). Upon stimulation, LPA receptors couple to multiple heterotrimeric G proteins (Gi, Gq, G12/13 alpha subunits) to elicit cellular responses, but the specific pathway that triggers chemotaxis in fibroblasts is unclear (Moolenaar et al, 1997;Mills and Moolenaar, 2003).…”
Section: Introductionmentioning
confidence: 99%